EXPLOITATION, REPAIR AND RESTORE OF WATER-COOLING BLOCKS OF BLAST STEEL-FURNACES IN REPAIR DEPARTMENTS OF RUP «BMZ» - M. V. Maksimtsov (Литьë и металлургия, 2010)
The processes of repair of water-cooled block blast steel furnace in repair shops of RUP “BMZ” are described in detail.